Use of optical techniques in the assment of the displacement field near the crack tip - Ribeiro, J.E. (2010)
A crack tip represents a highly singular stress field existing in a structural component. The evaluation of the associate strain gradient is difficult using experimental discrete methods. An efficient alternative relies on optical methods which are non contact and give continuous information about displacements fields and its derivatives for strain evaluation. This paper describes some experimental methods to fully characterize the displacement field near a crack tip existing in flat plates. Three optical field techniques based on image analysis were used in the present work; respectively ESPI (Electronic speckle pattern interferometry), MI (Moiré Interferometry), and DIC (digital image correlation). These methods present different resolutions which can be adjusted according to the expected strain gradient. While the first method depends on the laser wavelength, the second depends on the grid pitch and the last on the surface texture.